Preparation and use of plant medicines for farmers' health in Southwest Nigeria: socio-cultural, magico-religious and economic aspects - Oguntade Adegboyega E; Mafimisebi Taiwo E (BMC, 2010)
Abstract Agrarian rural dwellers in Nigeria produce about 95% of locally grown food commodities. The low accessibility to and affordability of orthodox medicine by rural dwellers and their need to keep healthy to be economically productive, have led to their dependence on traditional medicine. This paper posits an increasing acceptance of traditional medicine country-wide and advanced reasons for this trend. The fact that traditional medicine practitioners' concept of disease is on a wider plane vis-à-vis orthodox medicine practitioners' has culminated in some socio-cultural and magico-religious practices observed in preparation and use of plant medicines for farmers' health management. Possible scientific reasons were advanced for some of these practices to show the nexus between traditional medicine and orthodox medicine. The paper concludes that the psychological aspect of traditional medicine are reflected in its socio-cultural and magico-religious practices and suggests that government should fund research into traditional medicine to identify components of it that can be integrated into the national health system.